Economics Theory Through Applications - Cooper, Russell; John, Andrew; Open Textbook Library (Open Textbook Library, 2012)
Russell Cooper and Andrew John have written an economics text aimed directly at students from its very inception. You're thinking, "Yeah, sure. I've heard that before." This textbook, Economics: Theory Through Applications, centers around student needs and expectations through two premises: ... Students are motivated to study economics if they see that it relates to their own lives. ... Students learn best from an inductive approach, in which they are first confronted with a problem, and then led through the process of solving that problem. Many books claim to present economics in a way that is digestible for students; Russell and Andrew have truly created one from scratch. This textbook will assist you in increasing students' economic literacy both by developing their aptitude for economic thinking and by presenting key insights about economics that every educated individual should know. How? Russell and Andrew have done three things in this text to accomplish that goal: Applications Ahead of Theory: They present all the theory that is standard in Principles books. But by beginning with applications, students get to learn why this theory is needed. Learning through Repetition: Important tools appear over and over again, allowing students to learn from repetition and to see how one framework can be useful in many different contexts. A Student's Table of Contents vs. An Instructor's Table of Contents: There is no further proof that Russell and Andrew have created a book aimed specifically at educating students about economics than their two tables of contents.
Chapter 1: What Is Economics? -- Chapter 2: Microeconomics in Action -- Chapter 3: Macroeconomics in Action -- Chapter 4: Everyday Decisions -- Chapter 5: Life Decisions -- Chapter 6: eBay and craigslist -- Chapter 7: Where Do Prices Come From? -- Chapter 8: Why Do Prices Change? -- Chapter 9: Growing Jobs -- Chapter 10: Making and Losing Money on Wall Street -- Chapter 11: Raising the Wage Floor -- Chapter 12: Barriers to Trade and the Underground Economy -- Chapter 13: Superstars -- Chapter 14: Cleaning Up the Air and Using Up the Oil -- Chapter 15: Busting Up Monopolies -- Chapter 16: A Healthy Economy -- Chapter 17: Cars -- Chapter 18: The State of the Economy -- Chapter 19: The Interconnected Economy -- Chapter 20: Globalization and Competitiveness -- Chapter 21: Global Prosperity and Global Poverty -- Chapter 22: The Great Depression -- Chapter 23: Jobs in the Macroeconomy -- Chapter 24: Money: A User's Guide -- Chapter 25: Understanding the Fed -- Chapter 26: Inflations Big and Small -- Chapter 27: Income Taxes -- Chapter 28: Social Security -- Chapter 29: Balancing the Budget -- Chapter 30: The Global Financial Crisis -- Chapter 31: Toolkit
In English.
Description based on online resource
Keywords: Economics -- Textbooks